Preparation and wear properties of high-silicon high-vanadium wear-resistant alloy with nano pearlite matrix and carbides composite structure - Hongshen Xie; Wanqing Leng; Ming Li; Litao Yin; Zhou Li; Chenhui Zhu; Xuke Yao; Liujie Xu (Journal of Materials Research and Technology, 2024)
Combining high hardness carbide of high vanadium cast iron with nano pearlite, which has high strength and toughness, represents an innovative attempt to explore a new technology for preparing high vanadium alloy. In this study, a high-silicon high-vanadium wear-resistance alloy (HSHVWRA) was designed, incorporating a nano pearlite matrix and carbides composite structure. By increasing the vanadium content, numerous high hardness micrometer vanadium carbides were obtained The CCT curve was shifted to the left by increasing the silicon content in the alloy. Subsequently, the nano pearlite matrix was obtained by air cooling after austenite at 1100 °C. After heat treatment, the inter lamellar spacing of pearlite decreased from 500 to 1500 nm in the as-cast state to 50–200 nm. The heat treatment process significantly improved the wear resistance of HSHVWRA by obtaining a nano pearlite matrix. The weight loss due to abrasive wear in the nano pearlite matrix-based HSHVWRA was reduced by 26.9 % compared to the traditional micro-pearlite matrix-based alloy. In the impact wear test, the wear weight of the nano pearlite material was reduced by 63.7 % compared to the cast sample, resulting in a maximum relative wear resistance of 2.75. Nano pearlite has the ability to prevent crack initiation between the matrix and carbides and inhibit the propagation of fatigue cracks, thereby enhancing the fatigue resistance of the matrix. Additionally, with a higher number of layered sheets, nano pearlite can effectively withstand impact loads. Meanwhile, submicron carbides dispersed in the nano pearlite matrix contribute to a second phase strengthening role and cooperate with nano pearlite to enhance the wear resistance of the materials.